Toward long-term storage of nuclear materials in MOX fuels fabrication facility - Hirooka, Shun; Nakamichi, Shinya; Matsumoto, Taku; Tsuchimochi, Ryota; Murakami, Tatsutoshi (Frontiers in Nuclear Engineering, 2023)
Storage of plutonium (Pu)-containing materials requires extremely strict attention to physical safety and material accounting. For the emphasized importance of storage management, many reports are available in the public, e.g., experience in PuO2 storage in the UK and safety standards in the storage of Pu-containing materials in the US. Japan also stores plutonium, mainly in the form of uranium-Pu mixed oxide (MOX) mostly in powder form. Robust conditioning and storage arrangements must be adopted that are appropriate to the characteristics of the MOX, such as raw powder obtained by reprocessing of spent Light Water Reactor fuels, MOX samples from research and development on the remains of fuel fabrication, which can contain organic materials, and dry-recycled powder during fuel fabrication. A reduction in MOX fuel fabrications operations and experience in degradation of MOX containers during extended period of storage have led to JAEA to review the MOX storage arrangements in the Plutonium Fuel Development Center in Japan Atomic Energy Agency. The present work discusses the various nuclear materials, storage methods, experience in degradation of containers that occur during storage, and strategies for future long-term storage.